National Dialogue on Integrated Decentralized Food System Governance, Food Security, and Nutrition - Sok, Sao; Bernardo, Eisen; Sithirith, Mak (CGIAR, 2024)
WorldFish, CARD, IWMI, and CDRI hosted a National Dialogue on Integrated Decentralized Food System Governance in Phnom Penh. The event shared experiences from two pilot projects focusing on district-level governance and community-level food security, nutrition, and health. High-level officials, including Deputy Prime Minister Dr. Ouk Rabun, endorsed district Technical Working Groups piloted by AMD and CGIAR as innovations for improving governance, food security, and natural resource management. The approach aligns with Sub-decree No. 184 of 2019 and emphasizes linking district groups with provincial and national bodies. Officials recommended nationwide adoption for resilient food systems.